The Effects of Aerodumbbell Exercise Intervention on Weight loss, Body Fat Percentage, and Increased Muscle Mass in a Normal BMI Population - Suto Wijoyo Wisnu Teguh Purnomo; Siti Baitul Mukarromah; Hadi Hadi; Sri Sumartiningsih (Journal of Physical Education and Sports, 2026)
This study is to evaluate the effects of an aerodumbbell training intervention on weight reduction and body fat percentage in individuals with a normal Body Mass Index (BMI). This quasi-experimental study had 10 people with a normal BMI, allocated into a treatment group (n=5) and a control group (n=5). The treatment group participated in a 4-week aerodumbbell workout regimen at an intensity of 60-70% of maximal heart rate, with a frequency of three sessions per week, each lasting 60 minutes. Data from pretests and posttests, encompassing body weight (BW), body fat mass (BFM), and skeletal muscle mass (SMM), were subjected to descriptive and comparative statistical analyses. The research findings indicate that the treatment group exhibited a notable reduction in average body weight of 2.28 kg (p<0.05) and a decrease in average body fat mass of 3.94 kg (p<0.05), alongside an increase in average muscle mass of 1.66 kg (p<0.05). In contrast, the control group exhibited no notable alterations in any of the assessed characteristics. This study concludes that aerodumbbell exercise effectively reduces weight and body fat percentage while enhancing muscle mass in individuals with a normal BMI.